PENGELOLAAN SAMPAH PLASTIK MELALUI PEMBENTUKAN LEMBAGA BANK SAMPAH DI DESA KIDANG LOMBOK TENGAH - Fitri S, Adessa; M, Baiq Anisa Januari; Armisan, Corry; Putrawan, Deni; Ramadhan, Gilang; Pratama, Pandia; W, Ristansi Cahaya; Aminah, Siti; H, Tri Endri; S, Lolita Endang; Putrawan, Deni x (Universitas Mataram, 2024)
Plastic waste has become a serious problem in various areas, including Kidang Village, Lombok Tengah. This article discusses community empowerment activities in plastic waste management through the establishment of a Waste Bank and ecobrick making training. This activity aims to raise public awareness about the importance of proper plastic waste management and encourage active participation in preserving the environment. The method used in this activity is a participatory community approach. The stages of activity include initial survey, socialization and establishment of a Waste Bank, ecobrick making training, and monitoring and evaluation. The results showed that this activity was successful in increasing community knowledge and skills in managing plastic waste. The establishment of the Waste Bank and ecobrick making training are expected to encourage community participation in sustainable plastic waste management.